1992
DOI: 10.1016/0735-1097(92)90138-d
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of isovolumetric relaxation time as assessed by Doppler echocardiography predicts doxorubicin-induced systolic dysfunction in humans

Abstract: A reasonably sensitive and specific noninvasive test for doxorubicin cardiotoxicity is needed. In addition, few data exist on the short- and long-term effects of doxorubicin on diastolic filling. To determine if pulsed Doppler indexes of diastolic filling could predict doxorubicin-induced systolic dysfunction, 26 patients (mean age 48 +/- 12 years) were prospectively studied before receiving chemotherapy (control) and 3 weeks after obtaining cumulative doses of doxorubicin. In nine patients developing doxorubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
2
11

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 31 publications
3
78
2
11
Order By: Relevance
“…Greater than 37% increase in IVRT was 78% sensitive and 88% specific for predicting the ultimate development of doxorubicin-induced systolic dysfunction. 41 In a study of 20 patients receiving a mean cumulative dose of doxorubicin of 211 ± 82 mg/m 2 , pulsed tissue Doppler Imaging was reported to show mitral annulus IVRT \ 80 ms in 4 patients who had LVEF \ 50% appeared to outperform both standard Doppler IVRT and basal segment measurements, a finding the authors reported could be of interest to predict later impairment of LV function. 42 However, the published assessment of the MD Anderson Cancer Center has been that echo diastolic measures are more complex than systolic to obtain and interpret, reproducibility of echocardiographic measures of diastolic function has been problematic, and multiple diastolic measurements have had varying levels of success in identifying early cardiac toxicity.…”
Section: Echocardiography For Assessment Of Lvef Lvesvi and Risk Of Chfmentioning
confidence: 83%
See 1 more Smart Citation
“…Greater than 37% increase in IVRT was 78% sensitive and 88% specific for predicting the ultimate development of doxorubicin-induced systolic dysfunction. 41 In a study of 20 patients receiving a mean cumulative dose of doxorubicin of 211 ± 82 mg/m 2 , pulsed tissue Doppler Imaging was reported to show mitral annulus IVRT \ 80 ms in 4 patients who had LVEF \ 50% appeared to outperform both standard Doppler IVRT and basal segment measurements, a finding the authors reported could be of interest to predict later impairment of LV function. 42 However, the published assessment of the MD Anderson Cancer Center has been that echo diastolic measures are more complex than systolic to obtain and interpret, reproducibility of echocardiographic measures of diastolic function has been problematic, and multiple diastolic measurements have had varying levels of success in identifying early cardiac toxicity.…”
Section: Echocardiography For Assessment Of Lvef Lvesvi and Risk Of Chfmentioning
confidence: 83%
“…Echocardiographic evidence that LV diastolic dysfunction precedes resting systolic dysfunction has been reported, but does not appear to correlate with doxorubicin dosage or enhance prediction of CHF. [40][41][42] These parameters include prolonged isovolumetric relaxation period, reduction in peak flow velocity, and the ratio of early peak flow velocity/atrial peak flow velocity, as well as reduction in the deceleration rate of the early peak flow velocity. Stoddard et al 41 reported prolongation of isovolumetric relaxation time (IVRT) by Doppler echocardiography to predict doxorubicin-induced systolic dysfunction in a study of 26 patients.…”
Section: Echocardiography For Assessment Of Lvef Lvesvi and Risk Of Chfmentioning
confidence: 99%
“…Stoddard et al [12], in a study with 26 patients, found that early changes in a diastolic function parameter (i.e., a prolongation of isovolumetric relaxation time) following anthracycline therapy appeared before changes in systolic dysfunction parameters were identified. Additional studies have found changes in tissue Doppler parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the usefulness of several echocardiographic diastolic parameters in detecting anthracyclinerelated cardiac injury [12,13]. However, there is limited information from longitudinal studies about the incidence and evolution of diastolic dysfunction in a large and homogeneous cohort of patients treated with anthracyclines or anthracyclines plus trastuzumab.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that left ventricular ejection fraction and fractional shortening are insensitive to detection of doxorubicin cardiomyopathy (McKillop, Bristow 1983, Tjeerdsma, Meinardi 1999. Other measures were found useful in earlier detection of doxorubicin cardiomyopathy such as indices of diastolic dysfunction (Marchandise, Schroeder 1989, Stoddard, Seeger 1992, but considerable individual variability limits practical applicability in the clinical setting (Bu'Lock, Mott 1999) 2-dimensional strain echocardiography is a rapid, easy and objective way of measuring myocardial function. Strain is a measure of myocardial deformation, which is an intrinsic mechanical property.…”
Section: Discussion and Summarymentioning
confidence: 99%